STRATEGI GURU KELAS DALAM MENGINTEGRASIKAN MATERI FIKIH DAN IPA UNTUK MEWUJUDKAN PENDIDIKAN HOLISTIK DI MI AZZAINIYYAH - Ilham Maulana; Mulyawan Safwandy Nugraha (CV. Adiba Aisha Amira, 2026)
This study aims to analyze classroom teachers’ strategies in integrating Fiqh and Natural Sciences (IPA) to realize holistic education at MI Azzainiyyah. The research is motivated by the persistent dichotomy between religious subjects and general sciences in madrasah learning, which often causes Islamic Religious Education, particularly Fiqh, to be perceived as less contextual and less relevant to students’ daily lives. This study employed a qualitative approach with a case study design. Data were collected through in-depth interviews with the vice principal for curriculum and classroom teachers, classroom observations, and document analysis. The collected data were analyzed using an interactive analysis model consisting of data reduction, data display, and conclusion drawing. The findings indicate that the integration of Fiqh and Natural Sciences has been implemented contextually through flexible lesson planning, learning activities based on real-life examples and students’ experiences, and the reinforcement of school habituation programs. This integrative approach contributes to the development of holistic educational values encompassing cognitive, affective-spiritual, and psychomotor aspects. However, the implementation of integrative learning still faces challenges, particularly the lack of standardized integrative teaching materials and limited availability of learning media.